Educational inclusion and satisfaction of families of students with intellectual disabilities: a bibliometric study - Tebar-Yébana, Susana; Navarro-Mateu, Diego; Gómez-Domínguez, María Teresa; Gómez-Dominguez, Valentina (Frontiers in Psychology, 2024)
This bibliometric study scrutinises the corpus of scientific output within the Web of Science pertaining to familial satisfaction among parents raising children with intellectual disabilities, focusing specifically on the milieu of educational inclusion. The analysis discerns a discernible ascension in scholarly interest in this domain, encapsulating 77 papers emanating from 75 journals, incorporating an aggregate of 3,497 cited references. Our investigation delineated 354 researchers across 39 nations, underscoring the transnational purview of this scholarly endeavour. The United States emerged as the pre-eminent contributor, with Canada and the United Kingdom following suit. Collaboration on an international scale was notably led by the US, with the UK and Australia trailing in tandem. Prominent institutions were identified for their scholarly output; the University of Kansas led with four papers, followed closely